2015
DOI: 10.1016/j.juro.2015.05.075
|View full text |Cite
|
Sign up to set email alerts
|

The Ohmmeter Identifies the Site of Fluid Leakage during Artificial Urinary Sphincter Revision Surgery

Abstract: In cases of suspected fluid loss as a cause of artificial urinary sphincter malfunction an ohmmeter can identify the site of fluid loss during component revision surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Furthermore, several other studies have demonstrated the efficacy of PRB exchange in recurrent incontinence [6]. Studies using an ohmmeter or ultrasound to detect fluid-leak causes of mechanical failure have found that up to 70% of mechanical failures can be discovered via PRB interrogation [16,17]. These recent studies as well our institution's experience informed our decision to start systematic AUS revision with PRB inspection.…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, several other studies have demonstrated the efficacy of PRB exchange in recurrent incontinence [6]. Studies using an ohmmeter or ultrasound to detect fluid-leak causes of mechanical failure have found that up to 70% of mechanical failures can be discovered via PRB interrogation [16,17]. These recent studies as well our institution's experience informed our decision to start systematic AUS revision with PRB inspection.…”
Section: Discussionmentioning
confidence: 79%
“…In select cases where a component can be identified by either intra‐operative demonstration of a leak or by ohm‐meter and the original AUS was placed recently, single component replacement may be considered.…”
Section: Resultsmentioning
confidence: 99%
“…83,84 (C) Urethral sub-cuff atrophy is defined as a progressive loss of initial continence after AUS implantation in the absence of erosion, mechanical malfunction or leakage and/ or bladder-related causes leading to worsening of urinary continence.…”
Section: Resultsmentioning
confidence: 99%